W Zatoce Syreny: Lawinia i Strefa komfortu Tomasza Różyckiego - Gorczyńska, Małgorzata (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
An expression used in the title of my paper refers to several places in contemporary and ancient Italy: the Gulf of Naples, the shores of Lampedusa and Sicily, and the mouth of the Tiber River. These places form the background of the tragedy of African and Middle East refugees shown in poems by Tomasz Różycki: Lawinia (Lavinia) from the collection Litery (Letter by Letter, 2016) and Strefa komfortu (Comfort Zone) from the newest poetry book Kapitan X (Captain X, 2020). My detailed analysis of the two texts is an attempt to describe their formal and semantic complexity, especially their unique tone that mixes sharp irony with tender compassion.